The metaphysics of notation - Applebaum, Mark (St. Paul Innova, 2010)
This single DVD contains is a brief documentary that chronicles the inspiration, creation, and rendering of Mark Applebaums graphic score, The Metaphysics of Notation (2008). Additionally, the disc contains performance excerpts, two scrolling versions of the score and a set of stills excerpted from the notation.